City marketing: Development plan for the municipality of Heraklion, Crete - Theodore Metaxas; Ale Deffner; Marigianna Chalkiadaki (European Regional Science Association (ERSA), 2013)
Nowadays at a time which is characterized by the globalization and the economic crisis, the cities seek new ways to become competitive by demonstrating their comparative advantages. The competitiveness of the city however, cannot be enhanced only via spatial planning regulation. For that purpose, cities' consistent strategy for getting established as their users' preference, is to keep, highlight and project their special features that render them unique. Their weapon is the Strategic plan of City Marketing that aims to improve the city's image. City Marketing is not just a means of projecting the city to the general public. More importantly, it serves as a recourse for all those cities who have lost their identity, directing thus their growth according to a common vision. City Marketing is more useful today than at any other time period. The internationalization of the economy and the productive changes in the productive structure, mainly of the developed regions, have contributed to the creation of an interdependent competitive economic system in the cities, with the attraction of residents-investors-visitors as a reward. Modern consumers gradually become more and more experienced, mature, independent, demanding and sophisticated, and as a result they have high expectations from the cities that they live in-invest in-visit. Therefore, it became crucial to develop a Strategic City Marketing plan for the city of Helaklion in Crete, using as a guideline the modern perception of Strategic City Marketing. The ultimate goal was to provide the foundation, necessary for formulating a City Marketing plan, which would be based on the participatory process, so that it's modern conceptual content could be verified. By means of this plan, the city's advantages and disadvantages have emerged, as well as the needs and the wishes of all the demographic groups involved, so that the vision, the objectives and the implementation strategies could be formulated. Finally, as a culmination of this project, stands the creation of the city's brand-name, in order to showcase the identity of the city of Heraklion.
Keywords: 330; Place Marketing; branding; empirical research; Heraklion city; Greece